Expression, purification and crystallization of two major envelope proteins from white spot syndrome virus - Tang, Xuhua (International Union of Crystallography, 2007)
White spot syndrome virus (WSSV) is a major virulent pathogen known to infect penaeid shrimp and other crustaceans. VP26 and VP28, two major envelope proteins from WSSV, have been identified and overexpressed in Escherichia coli. In order to facilitate purification and crystallization, predicted N-terminal transmembrane regions of approximately 35 amino acids have been truncated from both VP26 and VP28. Truncated VP26 and VP28 and their corresponding SeMet-labelled proteins were purified and the SeMet proteins were crystallized by the hanging-drop vapour-diffusion method. Crystals of SeMet-labelled VP26 were obtained using a reservoir consisting of 0.1 M citric acid pH 3.5, 3.0 M sodium chloride and 1%(w/v) polyethylene glycol 3350, whereas SeMet VP28 was crystallized using a reservoir solution consisting of 25% polyethylene glycol 8000, 0.2 M calcium acetate, 0.1 M Na HEPES pH 7.5 and 1.5%(w/v) 1,2,3-heptanetriol. Crystals of SeMet-labelled VP26 diffract to 2.2 Å resolution and belong to space group R32, with unit-cell parameters a = b = 73.92, c = 199.31 Å. SeMet-labelled VP28 crystallizes in space group P2(1)2(1)2(1), with unit-cell parameters a = 105.33, b = 106.71, c = 200.37 Å, and diffracts to 2.0 Å resolution.